**Answers:**

And the answer is:

Sqrt (27/12) = sqrt(3*3*3/3*2*2)

Sqrt(3*3/2*2) = 3/2

The other one:

sqrt(1/36) = sqrt(1*1/6*6)=1/6

what the hell is that?

sq.rt.sign 27 over 12 boils down to:

3 sq.rt sign 3 all on top of 2 sq.rt. sign 3

then you have to get rid of the sq.rt sign on the bottom so multiply the whole thing times 2 sq.rt. sign 3 over 2 sq.rt sign 3

sq.rt. 1 over 36 = 1/6 because 1/6 x 1/6 = 1/36

This article contents is post by this website user, EduQnA.com doesn't promise its accuracy.

**More Questions & Answers...**